Vitamin D3 affects liver expression of pro-/anti-inflammatory cytokines and nitric oxide synthases in type 2 diabetes - Ihor Shymanskyi; Olha Lisakovska; Mykola Veliky; Olha Mezhenska; Vasyl Bilous; Andrii Siromolot; Anna Khomenko; Dmytro Labudzynskyi; Tetyana Horid’ko; Elvira Pasichna (Experimental Biology and Medicine)
Our objective was to study the effect of vitamin D3 (VD) on hepatocellular oxidative-nitrosative stress and pro/anti-inflammatory cytokines in relation to nitric oxide (NO) formation and NO synthase (NOS) levels in type 2 diabetes mellitus (T2DM). After T2DM induction by high-fat diet and a single streptozotocin injection (25 mg/kg b. w.), male Wistar rats were treated with/without VD (1,000 IU/kg b. w., 30 days). Oxidative stress/inflammation and NOS/NO were assessed by flow cytometry, RT-qPCR, western blotting, and ELISA. A 3.3-fold decrease in serum 25(OH)D3 was established in diabetic rats, suggesting their VD deficient status. T2DM was associated with excess reactive oxygen species (ROS; 2.4-fold) and NO (2.5-fold) production in hepatocytes paralleled by elevated levels of myeloperoxidase (1.7-fold), carbonylated (2.8-fold) and nitrotyrosylated (1.7-fold) proteins in liver tissue vs. control, indicative of oxidative-nitrosative stress. Low-grade inflammation in diabetic liver was confirmed by increased NF-κB transcriptional activity (1.24-fold) and mRNA expression of proinflammatory cytokines TNF-α (3.5-fold) and IL-1β (2.2-fold) with alleviating mRNAs of anti-inflammatory cytokines IL-4 (1.7-fold) and IL-10 (2.6-fold), while TGF-β1 expression raised 1.4-fold vs. control. Higher iNOS and eNOS mRNAs (2.7- and 3.3-fold, respectively) and protein (2.1- and 3.2-fold, respectively) levels, as well as NOS activity (1.6-fold) were found in diabetic liver. VD supplementation restored 25(OH)D3, partially normalized NF-κB transcriptional activity and pro/anti-inflammatory cytokines, lowered hepatocellular ROS/NO, and oxidative protein modifications. However, VD had no effect on eNOS, IL-10 and TGF-β1 mRNAs. It also led to a further increase in myeloperoxidase, eNOS and iNOS proteins and NOS activity compared to diabetes. In conclusion, abnormal oxidative metabolism in T2DM is associated with enhanced NF-κB/NOS/NO response, which can be partially attenuated by VD treatment via normalization of pro-oxidative/pro-inflammatory processes. The paradoxical sustained increase in NOS expression in the presence of VD antioxidant activity likely improves hepatocellular NO bioavailability, ultimately reducing T2DM-associated liver injury.